1996
DOI: 10.1021/jm960313y
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of S-Adenosyl-l-homocysteine Hydrolase by Amide and Ester Derivatives of Adenosine-5‘-carboxylic Acid

Abstract: S-Adenosyl-L-homocysteine (AdoHcy) hydrolase has been shown to have (5'/6') hydrolytic activity with vinyl (5') or homovinyl (6') halides derived from adenosine (Ado). This hydrolytic activity is independent of its 3'-oxidative activity. The vinyl (or homovinyl) halides are converted into 5'(or 6')-carboxaldehydes by the hydrolytic activity of the enzyme, and inactivation occurs via the oxidative activity. Amide and ester derivatives of Ado-5'-carboxylic acid were prepared to further probe the hydrolytic capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The 6‘( E )-(halohomovinyl)adenosine derivatives D were shown to inactivate AdoHcy hydrolase by catalyzed addition of water to the 5‘,6‘-double bond and generation of the labile homoadenosine-6‘-carboxaldehyde (loss of a proton and halide from C6‘) the 4‘-ethynyl (acetylenic) analogue, and amide or ester derivatives of adenosine- 5‘-carboxylic acid but no evidence for enzyme-mediated hydrolysis of the amide or ester compounds was observed .…”
Section: Introductionmentioning
confidence: 99%
“…The 6‘( E )-(halohomovinyl)adenosine derivatives D were shown to inactivate AdoHcy hydrolase by catalyzed addition of water to the 5‘,6‘-double bond and generation of the labile homoadenosine-6‘-carboxaldehyde (loss of a proton and halide from C6‘) the 4‘-ethynyl (acetylenic) analogue, and amide or ester derivatives of adenosine- 5‘-carboxylic acid but no evidence for enzyme-mediated hydrolysis of the amide or ester compounds was observed .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of the 5‘-hydroxymethylene of nucleosides to 5‘-carboxylates is an essential step in the preparation of a number of biologically active molecules . There are relatively few methods describing the general preparation of such nucleoside-5‘-carboxylic acids.…”
mentioning
confidence: 99%
“…11 In contrast with these results, 10 and the enzymatic hydrolysis of oximes, 9 amide and ester derivatives of adenosine-5′-carboxylic acid underwent oxidation at C3′ by AdoHcy hydrolase (type I, NAD + cofactor-depletion inhibitors 2b ) without observed hydrolysis to the carboxylic acid. 12 We now report analogues of ZDDFA and EDDH-HAs that do not contain the 3′-hydroxyl group (which is oxidized to give 3′-keto intermediates) and their interaction with AdoHcy hydrolase. The 3′-deoxy analogues have major differences in stereoelectronic effects and lack a hydrogen-bond acceptor at C3′.…”
Section: Introductionmentioning
confidence: 94%
“…We had demonstrated that the ( E )-5‘,6‘-didehydro-6‘-deoxy-6‘-halohomoadenosines10a E (EDDHHAs), and especially the homovinyl fluoride 10b F (EDDFHA), could undergo addition of water at C5‘ and C6‘ by AdoHcy hydrolase (hydrolytic activity) without prior oxidation at C3‘ . In contrast with these results, and the enzymatic hydrolysis of oximes, amide and ester derivatives of adenosine-5‘-carboxylic acid underwent oxidation at C3‘ by AdoHcy hydrolase (type I, NAD + cofactor-depletion inhibitors 2b ) without observed hydrolysis to the carboxylic acid . We now report analogues of ZDDFA and EDDHHAs that do not contain the 3‘-hydroxyl group (which is oxidized to give 3‘-keto intermediates) and their interaction with AdoHcy hydrolase.…”
Section: Introductionmentioning
confidence: 99%